Does population screening for Chlamydia trachomatis raise anxiety among those tested? Findings from a population based chlamydia screening study - Low Nicola; Graham Anna; Sanford Emma; Mills Nicola; Campbell Rona; Peters Tim J (BMC, 2006)
Abstract Background The advent of urine testing for Chlamydia trachomatis has raised the possibility of large-scale screening for this sexually transmitted infection, which is now the most common in the United Kingdom. The purpose of this study was to investigate the effect of an invitation to be screened for chlamydia and of receiving a negative result on levels of anxiety, depression and self-esteem. Methods 19,773 men and women aged 16 to 39 years, selected at random from 27 general practices in two large city areas (Bristol and Birmingham) were invited by post to send home-collected urine samples or vulvo-vaginal swabs for chlamydia testing. Questionnaires enquiring about anxiety, depression and self-esteem were sent to random samples of those offered screening: one month before the dispatch of invitations; when participants returned samples; and after receiving a negative result. Results Home screening was associated with an overall reduction in anxiety scores. An invitation to participate did not increase anxiety levels. Anxiety scores in men were lower after receiving the invitation than at baseline. Amongst women anxiety was reduced after receipt of negative test results. Neither depression nor self-esteem scores were affected by screening. Conclusion Postal screening for chlamydia does not appear to have a negative impact on overall psychological well-being and can lead to a decrease in anxiety levels among respondents. There is, however, a clear difference between men and women in when this reduction occurs.